Synchronous primary adenocarcinoma and gastrointestinal stromal tumor in the stomach: A report of two cases - Sema BİRCAN; Özden CANDIR; Şerife AYDIN; Şirin BAŞPINAR; Mahmut BÜLBÜL; Nilgün KAPUCUOĞLU; Nermin KARAHAN; Metin ÇİRİŞ (Turkish Journal of Gastroenterology, 2019)
-